The phenotypic spectrum of the Cornelia de Lange‐like “Alazami‐Yuan syndrome”: A case report of the 7th diagnosed individual and review of the literature - Annie Pappas; Mary Mooney; Katherine Kohnen; Joshua W. Owens; Wenying Zhang; Robert J. Hopkin; Amelle Shillington (Clinical Case Reports)
Key Clinical Message We present a 17‐year‐old female with a childhood clinical diagnosis of Cornelia de Lange Syndrome (CdLS), however later genetic testing identified compound heterozygous variants in TAF6, consistent with AYS. This case report adds to the phenotypic spectrum observed in AYS, and draws connections to transcriptional pathways between CdLS and AYS.